Building a European 'network of networks' for stroke clinical research – The European Stroke Organisation Trials Alliance (ESOTA). (September 2019) - Kelly, Peter; Salman, Rustam A; Arsovska, Anita; Dippel, Diederik WJ; Fischer, Urs; Ford, Gary A; Fuentes, Blanca; Lemmens, Robin; Marshall, John C; Nederkoorn, Paul J; Robinson, Thompson; Weimar, Christian; et al.
Promoting research to improve stroke prevention, acute care, and recovery is a key mission of the European Stroke Organisation (ESO). Stroke research networks may increase efficiencies and reduce waste in randomised clinical trials of stroke treatments. Several European countries have established national or regional stroke research networks, or have informal groups or stroke registers which may serve as a foundation for establishing a research network. To increase international collaboration on randomised trials for stroke in Europe, the ESO Trials Network Committee is leading the development of an alliance of national networks, the ESO Trials Alliance (ESOTA). Following initial consultation work in 2017, this paper describes an overview of progress to date in the first year of ESOTA activity. Beginning with five founding networks in England, Ireland, Netherlands, Spain, and Switzerland, ESOTA aims to gradually grow, ultimately including several hundred stroke centres and affiliated investigators working collectively on randomised trials of new stroke treatments.